Selection of contractor using analytical hierarchy process (AHP) - Nurul Syafiqah, Zaini (2018)
Construction projects are now progressing rapidly in Malaysia and have been as one of an important factor in contributing increasing economic country. Because of that, contractor selection is an important aspect in construction sector especially for client or parties involve that need to hire the best contractor to manage and complete their project within time and cost given also with good quality. Furthermore, without a suitable method use in selection of contractor, it for sure will affect the completion of whole project. In this study, I am doing research about the use of the analytical hierarchy process (AHP) as a decision support model to select contractor. The AHP allows constructing decision as hierarchies and each criterion can be evaluated through weighted determined by the expert in construction field. The purpose of this study is to develop the main criteria used by client in selection of contractors also identify the weighted criteria by using AHP method from current practice in Malaysia. Besides, this method is one of the decision-making that is necessary to eliminate the risks of project failure due to poor contractor’s performance.